PENGARUH PROGRAM KELUARGA HARAPAN (PKH) TERHADAP PENGENTASAN KEMISKINAN DI KECAMATAN RAMBANG KAPAK TENGAH - Rika Rahmadina Putri; Evi Asriani (Program Studi Perbankan Syariah, 2021)
This study aims to determine the effect of the family of hope program on poverty alleviation in Rambang Kapak Tengah District. The sample in this study was selected very poor households that received PKH assistance in Rambang Kapak Tengah District, amounting to 110 people. The results showed that the partial test (t test) can be seen the correlation between x and y with a t value of 18.320 while the t table for 110 respondents is 1.65882, while the significant is 0.00 < 0.05, then the hypothesis is accepted. While the results of the r2 determination test show that the value of r square is 0.757 or 75%, then the family program of hope (x) has an effect on poverty alleviation by 75% and the remaining 24.3% is influenced by other variables.